Comparison between first and second wave of COVID-19 outbreak in older people: the COPE multicentre European observational cohort study. (23rd August 2022) - Verduri, Alessia; Short, Roxanna; Carter, Ben; Braude, Philip; Vilches-Moraga, Arturo; Quinn, Terence J; Collins, Jemima; Lumsden, Jane; McCarthy, Kathryn; Evans, Louis; Myint, Phyo K; Hewitt, Jonathan; et al.
Abstract: Background: Effective shielding measures and virus mutations have progressively modified the disease between the waves, likewise healthcare systems have adapted to the outbreak. Our aim was to compare clinical outcomes for older people with COVID-19 in Wave 1 (W1) and Wave 2 (W2). Methods: All data, including the Clinical Frailty Scale (CFS), were collected for COVID-19 consecutive patients, aged ≥65, from 13 hospitals, in W1 (February–June 2020) and W2 (October 2020–March 2021). The primary outcome was mortality (time to mortality and 28-day mortality). Data were analysed with multilevel Cox proportional hazards, linear and logistic regression models, adjusted for wave baseline demographic and clinical characteristics. Results: Data from 611 people admitted in W2 were added to and compared with data collected during W1 ( N  = 1340). Patients admitted in W2 were of similar age, median (interquartile range), W2 = 79 (73–84); W1 = 80 (74–86); had a greater proportion of men (59.4% vs. 53.0%); had lower 28-day mortality (29.1% vs. 40.0%), compared to W1. For combined W1–W2 sample, W2 was independently associated with improved survival: time-to-mortality adjusted hazard ratio (aHR) = 0.78 [95% confidence interval (CI) 0.65–0.93], 28-day mortality adjusted odds ratio = 0.80 (95% CI 0.62–1.03). W2 was associated with increased length of hospital stay aHR = 0.69 (95% CI 0.59–0.81). Patients in W2 were less frail, CFS [adjusted mean difference (aMD) = −0.50, 95% CI −0.81, −0.18], as well as presented with lower C-reactive protein (aMD = −22.52, 95% CI −32.00, −13.04). Conclusions: COVID-19 older adults in W2 were less likely to die than during W1. Patients presented to hospital during W2 were less frail and with lower disease severity and less likely to have renal decline.